Hydrogels Recent Advances - Thakur, Vijay Kumar; Thakur, Manju Kumari; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book discusses recent advances in hydrogels, including their generation and applications and presents a compendium of fundamental concepts. It highlights the most important hydrogel materials, including physical hydrogels, chemical hydrogels, and nanohydrogels and explores the development of hydrogel-based novel materials that respond to external stimuli, such as temperature, pressure, pH, light, biochemicals or magnetism, which represent a new class of intelligent materials. With their multiple cooperative functions, hydrogel-based materials exhibit different potential applications ranging from biomedical engineering to water purification systems. This book covers key topics including superabsorbent polymer hydrogel; intelligent hydrogels for drug delivery; hydrogels from catechol-conjugated materials; nanomaterials loaded hydrogel; electrospinning of hydrogels; biopolymers-based hydrogels; injectable hydrogels; interpenetrating-polymer-network hydrogels: radiation- and sonochemical synthesis of micro/nano/macroscopic hydrogels; DNA-based hydrogels; and multifunctional applications of hydrogels. It will prove a valuable resource for researchers working in industry and academia alike.
Intelligent Hydrogels For Controlled Drug Delivery -- Hydrogels From Catechol-Conjugated Polymeric Materials -- Super Absorbent Polymer Hydrogels -- Hydrogel-Based Strategies For Stem Cell Therapy -- Protein And Nanoparticle Loaded Hydrogels Studied By Small Angle Scattering And Rheology Techniques -- Preparation, Properties And Applications Of Hydrogels: A Review -- Hydrogel-Based Stimuli-Responsive Functionalized Graft Copolymers For The Controlled Delivery Of 5-Fluorouracil , An Anticancer Drug -- Emerging Technology In Medical Applications Of Hydrogel -- Electro Spinning Of Hydrogels For Biomedical Applications -- Polyvinyl Alcohol Hydrogels: Tunable Scaffolds For Tissue Engineering -- Cellulose Hydrogels As Sustainable Materials Regenerated From Waste -- Injectable Hydrogels For Cartilage Regeneration -- Poly (Vinyl Alcohol)/Polysaccharides Hydrogel Materials For Wound Healing And Waste Water Treatment -- Hydrogels : Synthesis Characterization And Applications -- Radiation- And Sonochemical Synthesis Of Nano-, Micro- And Macroscopic Hydrogels -- Dna Based Hydrogels: An Approach For Multifunctional Bio-Applications -- Stimuli-Responsive Hydrogel Film Changing In Adsorption-Desorption Of Nanoparticles Reversibly -- Various Functional And Stimuli-Responsive Hydrogel Based On Polyaspartamides -- Interpenetrating-Polymer-Network Hydrogels: Smart Materials For Biomedical Applications.
Keywords: Polymers; Microtechnology; Microelectromechanical systems; Biotechnology; Nanochemistry; Nanoscience; Nanotechnology; Polymers; Microsystems and MEMS; Biotechnology; Nanochemistry; Nanophysics; Nanotechnology